circRNA-DURSA regulates trophoblast apoptosis via miR-760-HIST1H2BE axis in unexplained recurrent spontaneous abortion - Minyue Tang; Long Bai; Zhe Wan; Shan Wan; Yu Xiang; Yeqing Qian; Long Cui; Jiali You; Xiaoling Hu; Fan Qu; Yimin Zhu (Elsevier, 2021)
Unexplained recurrent spontaneous abortion (URSA) is one of the most intractable clinical challenges in reproduction. As a specific type of endogenous non-coding RNA, circular RNAs (circRNAs) have great pre-clinical diagnostic and therapeutic values in diseases. Recently, thousands of circRNAs were detected in human pre-implantation embryos, indicating that circRNAs potentially have important regulatory functions. However, the roles of circRNAs in URSA remain largely unknown. In this study, we elucidated deregulated circRNA expression and distinct competing endogenous RNA (ceRNA) networks by comparing URSA placental villus with that of patients with normal pregnancy using microarrays. We characterized a distinct circRNA, circRNA-0050703, which is downregulated in URSA placental villus (thus we named it circRNA-DURSA). Silencing of circRNA-DURSA results in trophoblast cell apoptosis in vitro. Furthermore, mechanistic dissection revealed that circRNA-DURSA exerts its effects by competitively binding to miR-760, which post-transcriptionally targets HIST1H2BE. Additionally, after circRNA-DURSA silencing in vivo, the numbers of implanted embryos decreased significantly. These results reveal the regulatory roles of circRNA-DURSA in trophoblasts and identified a distinct circRNA-DURSA/miR-760/HIST1H2BE axis as potentially important diagnostic and therapeutic targets for URSA treatment.